Strukturen verantwortlichen Lebens: die Bedeutung Heinz Eduard Tödts für die theologische Ethik : Vortrag bei der Akademischen Gedenkfeier in Heidelberg am 6. Mai 1992 - Huber, Wolfgang (Zeitschrift für evangelische Ethik, 1992)
The article describes »structures ofresponsible life« in Tödt's theological thinking. (1) As a professor Tödt taught an ethos of matureself responsibility. (2) He was led from exegesis to social ethics by the task of interpreting the gospel in our present time. Tödt explores analogies and differences between options of our present time and the fundamental directions ofChristian faith, especially through such topics as peace and human rights. (3) In a world characterized by modern science and technology, human beings are themselves responsible for the norms of their actions in the sense of a cooperatio hominis cum deo that responds to God. (4) Tödt's ethical heory of moral reasoning tends to an ethic of action. (5) As an historian, the theologian is also accountable for hisfundamental world view. For Tödt, in his research of the Bonhoeffer-Dohnanyi circle's resistance, taking sides with the victims was central.